2017
DOI: 10.1088/1748-605x/aa50a1
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin freeze casting of biomimetic titanium alloy with anisotropic and gradient pore structure

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Abstract. Titanium metal and its alloys are materials commonly used for dental and orthopaedic implants. However, due to large difference in properties between the titanium metal and the natural bone, stress shielding has been observed around the surround area, resulting in bone atrophy, and thus has raised concerns of the use of this material. Ideally implant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Introducing an initial gelation of the solvent by adding gelatin and leaving it to harden causes the medium in which the ice grows to change, thereby changing the final morphology of the ice crystals and thus the resulting pores . While the macroporosity of the gelated structures are still lamellar and the perpendicular pore shape is overall ellipsoidal, as is evident from Figure , the general morphology is significantly different.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Introducing an initial gelation of the solvent by adding gelatin and leaving it to harden causes the medium in which the ice grows to change, thereby changing the final morphology of the ice crystals and thus the resulting pores . While the macroporosity of the gelated structures are still lamellar and the perpendicular pore shape is overall ellipsoidal, as is evident from Figure , the general morphology is significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…Combining gelation and freeze‐casting using gelatin was introduced by Fukushima et al, who showed that initial gelation of samples completely alters the morphology of the pores while achieving complex shapes throughout the entire ceramic body. The gelated freeze‐cast structures have, however, primarily been used for processing of insulating materials, membranes, and biomedical purposes, where the latter utilizes the hierarchical nature of freeze‐cast structures, as previously mentioned. However, until now gelated freeze‐cast structures have been processed using primarily static freezing profiles .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the inverse relationship between pore size and mechanical properties was confirmed, temperature influence was not detected. 87 Although the three components are usually combined, it is also possible to exploit the freeze-casting technique without the presence of a powder, which results in a physical but not a chemical gradient. An anisotropic frozen alginate scaffold was produced by gradual cooling of the polymer solution, lyophilization, and final immersion in a solution with a high concentration of CaCl 2 for structural stabilization.…”
Section: Intrinsic-gradient Approachmentioning
confidence: 99%